Nutritional considerations for elite golf: a narrative review - Berlin, N.; Cooke, M. B.; Belski, R. (Nutrients, 2023)
Golf is predominantly a skill-based sport where technical aspects are regarded as a priority area for improving performance. At present, most of the existing literature has focused on improving a player`s physicality, endurance and technical attributes in an effort to enhance performance. While important, the role of nutrition in elite golf has received little attention to date. The energy demands of the sport can vary depending on the level of the individual (recreational-professional), with distances of up to 20 km being covered and the time spent on the course ranging approximately 4-8 h each day. Like other sports, a focus on pre-game, during and post-game nutrition, including hydration, is integral to ensuring that individuals are adequately fuelled, hydrated and optimally recovered. For the elite athletes who travel extensively to international tournaments, it is important to understand the additional impact of travel on the body and consider the role nutrition can play in preventing illness and ensuring minimal disruption to golf performance. Lastly, the role of dietary supplements to enhance the performance of golfers is also important to consider. This review aims to consolidate the findings of the existing research focusing on nutrition strategies for golf performance and identify areas for potential future research.